(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective:To evaluate the analgesic effect of unilateral ultrasound-guided transversalis fascia plane (TFP) block using 0.25% ropivacaine during laparoscopic mesh repair for inguinal hernia. Methods: A randomized controlled clinical trial was conducted on 64 patients from March 2025 to September 2025 at Hanoi Medical University Hospital. Patients were divided into two groups: Group 1 (received TFP block) and Group 2 (control group, no block). The monitored parameters included ANIm index, heart rate, blood pressure, and intraoperative fentanyl consumption. Results:The TFP block group showed significantly higher ANIm values at all time points following skin incision compared to the control group (p < 0.001). The mean total fentanyl consumption was significantly lower in the TFP group (2.16 mcg/kg vs. 4.04 mcg/kg; p < 0.01). The mean onset time of TFP block was 4.31 ± 1.09 minutes. Conclusion: Ultrasound-guided TFP block is an effective, safe, and feasible method for intraoperative analgesia in laparoscopic hernia repair.